Selection of Alternative Locations for Rubber Weirs to Fulfill Clean Water needs in Rembang Regency - Adi, Henny Pratiwi; Wahyudi, Slamet Imam; Wahyudi, Rahmatia Sarah (ASTONJADRO, 2023)
Rembang Regency is one of the areas in Central Java that often faces the problem of lack of clean water, especially during the dry season. One of the innovations that can be applied to overcome the problems in Rembang Regency is to make a rubber weir. This study aims to consider and choose the location of the rubber weir which is planned to be built in the Kaliori District. There are 6 (six) criteria used in considering the selection of a rubber weir location and 3 (three) alternative location of weir. The data is then processed using the Analytical Hierarchy Process (AHP) method. The results showed that the most important criteria started from the ease of operational access (0.260), seawater intrusion (0.197), topographic considerations (0.161), social aspects (0.136), distance from water management installations (0.129), and the importance of fishing boats (0.117). As for Location 3, which is 300 m near the Dukuh Mbancang bridge, Tambakagung Village is the best alternative to be the location for the construction of a rubber weir. This is because the location has a straight river path and easy access and does not interfere with fishing activities.